Pneumothorax Causing Pneumoperitoneum: Role of Surgical Intervention - Fernanda Duarte; Jessica Wentling; Humayun Anjum; Joseph Varon; Salim Surani (Case Reports in Critical Care)
The most common cause of a pneumoperitoneum is a perforation of a hollow viscus and the treatment is an exploratory laparotomy; nevertheless, not all pneumoperitoneums are due to a perforation and not all of them need surgical intervention. We hereby present a case of pneumoperitoneum due to a diaphragmatic defect, which allowed air from a pneumothorax to escape through the diaphragmatic hernia into the abdominal cavity.